A Homozygous Frameshift Mutation in the HOXC13 Gene Underlies Pure Hair and Nail Ectodermal Dysplasia in a Syrian Family. Issue 4 (5th March 2013) - Farooq, Muhammad; Kurban, Mazen; Fujimoto, Atsushi; Fujikawa, Hiroki; Abbas, Ossama; Nemer, Georges; Saliba, Jessica; Sleiman, Rima; Tofaili, Mona; Kibbi, Abdul‐Ghani; Ito, Masaaki; Shimomura, Yutaka
<x xml:space="preserve">Abstract</x> In this study, we analyzed a consanguineous Syrian family with an affected girl with pure hair and nail ectodermal dysplasia, which is a rare genetic disorder characterized by alopecia and nail dystrophy since birth. Linkage studies and direct sequencing analysis led to the identification of a homozygous frameshift mutation (c.355delC; p.Leu119Trpfs*20) in the HOXC13 gene of the patient. In vitro studies in cultured cells demonstrated loss of function of the mutant HOXC13 protein. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>